The effect of the(Jerome Brunner Exploration) and the (Hilda Tapa inductive) models in the immediate and delayed achievement for the science subject of the eighth primary grade at Theiban district - Mussabeh, Ibraheem (Dirasat: Educational Sciences, 2020)
This study aimed to investigate the effect of using the Jerome Burner Exploration and Hilda Tapa Inductive models on the immediate and delayed achievement of the science subject of the eighth grade in the Theban district. The study sample contains 103 students (Male and Female) divided into 4 classes, two classes were randomly selected to be examined according to both models. For achieving the study’s purposes, a test was prepared that included multiple-choice questions. The results showed that there were significant statistical differences in the immediate and delayed achievement depending on the teaching methods and gender, the differences were in favour of the exploration model and females. Also, there were no differences related to the interaction between the teaching process and gender. Based on the results, the researcher recommended that science subjects teachers use and apply various modern teaching models as the exploration and inductive models in teaching all science subjects.